ALUMINIUM ANALYSIS IN EYE SHADOW USING ATOMIC ABSORPTION SPECTROPHOTOMETER - Rini Ambarwati (Journal of Science Innovare, 2019)
Industry is a human endeavor so that goods obtained from nature can be utilized as products that have a sale value and have a profitable profit in economic terms. Material from nature has chemicals that can be used for certain purposes, such as food, fuel, fuel, fertilizer, cosmetics, etc. so that human life becomes more comfortable. A chemical industry must pay attention to environmental sustainability and is expected to process materials that are safe for the environment, as well as products produced that are environmentally friendly. In the modern cosmetics industry, eyeshadow added pearly substances that have a shiny and radiant effect, in accordance with the current trend. Pearls derived from nature are Guanine, which comes from marine fish scales, are transparent and shiny crystals like pearls. Because Guanine is difficult to obtain, the producers replace it by adding synthetic pearls, including Aluminum metal powder. Aluminum is a metal used for basic materials of household appliances, but is contained in eyeshadow which functions as a pearling agent. Research on aluminum in eye shadow cosmetics has been carried out on the market. Quantitative analysis was carried out with Atomic Absorption Spectrophotometer, the results obtained showed the presence of Aluminum with the results of all eyeshadow used as samples containing Aluminum, but the level was still below the permissible level of 10%. Aluminum content contained in the eyeshadow used as a sample is between 0.35 mg / gram-16.952 mg/gram or 0.35% -1.69%. The smallest one is in the Gold E color eyeshadow brand and the highest one in the Gold B brand eyeshadow